Transformasi Identitas Etnis Melalui Konversi Keyakinan di Masyarakat Pontianak Kalimantan Barat - Muhammad Tisna Nugraha (IAIN Pekalongan, 2018)
This paper aims to explain the phenomenon of the fragility of the concept of ethnic identity in a multicultural society. Ethnic identity does not exclusively refer to something that is permanently attached to an individual. Rather, it also has to do with something that experiences development and transformation on the basis of the individual’s religious belief (religion). Indeed, ethnic identity oftentimes is associated with differences in race, religion, birthplace, and historical background. These differences, however, do not mater when individuals convert to Islam. Conversion to Islam as a consequence affects the extent to which individuals’ different ethnic identity is recognized as part of other ethnic identities. We conducted this study among ethnic Dayaks, Malays and Chinese in Pontianak, West Kalimantan. Data were obtained by means of interviews, observation and documentation. The main finding of the study reveals that ethnic backgrounds did not play a convincing role in the practice of multilateral social interactions. In this context, ethno-religious similarity more so than other factors easily unite members of ethnic groups. Here then lies the cycle of ethnicity that has returned to the classical phase wherein ethnic formation is not only determined by historical background, territory, and blood relations, but also religion.